Plotting of compaction curves of ceramic powders on the basis of one-parameter pressing equations; Refractories and Industrial Ceramics; Vol. 42, № 1-2 - Khasanov O. L. Oleg Leonidovich (2001, 2001)
A one-parameter equation that describes pressing of ceramic powders in the dimensionless coordinates "relative pressing pressure - relative density of the compact" is suggested. It is shown that the boundary conditions are correctly obeyed for such an equation. The correctness of the initial conditions is provided by the developed method for plotting the compaction curves. The consecutive unloading of the powder body envisaged by the method makes it possible to determine the contribution of the elastic interaction of the particles to compaction. The true compaction curve of ZrO2 - 5% Y2O3 nanopowder is well described by a one-parameter logarithmic equation